The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.jchromb.2019.121713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure variation on the efficiency of supercritical fluid extraction of wild carrot (Daucus carota subsp. maritimus) extracts

Abstract: The present study was conducted to check the comparative qualities of essential oils prepared by hydrodistillation (HD) and supercritical fluid techniques. It constitutes the first attempt to investigate the chemical composition of Daucus carota subsp. maritimus extracts using supercritical fluid technology (SFE) as an environmentally clean innovative method of extraction. The effect of pressure on the nature of extractable substances from wild carrot has been performed at a constant temperature of 50°C and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The main constituents of D. carota subsp. maritimus and D. carota "Nantes" EOs (from Turkey) reported by Majdoub, et al [49] and Keser, et al [50] were geranyl acetate, β-bisabolene, γ-bisabolene, terpinolene, elemicin, myristicin, 5-caffeoylquinic acid, 5-feruoylquinic, and dicaffeic acid. In our study, instead of carotol sesquiterpene, reported by Valente, et al [8], cariophyllene [m/z = 41, 55, 69, 79, 91, 119, 133, 147, 161, 175, and 189], cariophyllene oxide and farnesene sesquiterpenes were found.…”
Section: Active Components By Gc-ms Analysismentioning
confidence: 88%
“…The main constituents of D. carota subsp. maritimus and D. carota "Nantes" EOs (from Turkey) reported by Majdoub, et al [49] and Keser, et al [50] were geranyl acetate, β-bisabolene, γ-bisabolene, terpinolene, elemicin, myristicin, 5-caffeoylquinic acid, 5-feruoylquinic, and dicaffeic acid. In our study, instead of carotol sesquiterpene, reported by Valente, et al [8], cariophyllene [m/z = 41, 55, 69, 79, 91, 119, 133, 147, 161, 175, and 189], cariophyllene oxide and farnesene sesquiterpenes were found.…”
Section: Active Components By Gc-ms Analysismentioning
confidence: 88%
“…At a temperature of 40 °C, extraction was only significant at a pressure of 350 bar. Majdoub et al [ 87 ] found similar effects when raising the pressure from 100 to 300 bar at a constant temperature of 50 °C for obtaining extracts of Daucus carota.…”
Section: Resultsmentioning
confidence: 79%
“…Increasing the pressure, increases the density, and consequently increases the contact surface between the extractable compounds and the extraction solvent 37 , 38 . Main effect charts (Fig.…”
Section: Resultsmentioning
confidence: 99%